One swallow does not make a summer: Expansions on Gagné`s six constituent elements for talent development programs - Grassinger, R. (Talent Development & Excellence, 2011)
1. Enriched curriculum / training program 2. Clear and challenging excellence goal 3. Selective access criteria 4. Systematic and regular practice 5. Regular and objective performance assessment of progress 6. Personalized accelerated pacing